Becoming mathematical: Designing a curriculum for a mathematics club. - Lampen, E.; Brodie, K. (My University, 2020)
Mathematics clubs are becoming increasingly researched in South Africa, yet what might constitute a curriculum for such clubs has not been discussed. We present and analyse a curriculum design for clubs that we set up and worked with over three years. The goals of the clubs were to foster strong mathematical proficiency, identities and agency among learners through supporting their enjoyment of mathematics as a useful way to make sense of the world. We therefore developed a curriculum where learners could become and be ‘mathematical’, through drawing on both their everyday reasoning and the mathematics that they learned in school. Our analysis suggests an emergent, responsive curriculum, with tasks that can be categorised as: (1) becoming mathematical with everyday tasks, (2) becoming mathematical about mathematics, (3) being mathematical and making mathematics, and (4) mathematics. We argue that through such a curriculum, we can develop mathematical reasoning on the basis of learners’ everyday reasoning in ways that support their mathematical proficiency, identities and agency.